Incidence of primary exercise headache in resistance trained athletes - Noormohammadpour, P.; Shafiei, M.; Shahi, M. H. P.; Rostami, M.; Akbari-Fakhrabadi, M.; Memari, A. H.; Mansournia, M. A.; Ghadimi, E.; Sadeghian, E.; Kordi, R. (Asian Journal of Sports Medicine, 2017)
Objectives: The aim of this study was to examine the incidence and patterns of primary exercise headache (PEH) in resistance trained male athletes. PEH is observed particularly during or after severe physical exercise and lasts up to 48 hours. While the focus of the literature has mainly been on the prevalence of PEH in the general population, few studies on athlete populations have been conducted so far. Therefore in a cohort study we examined the incidence and patterns of PEH in resistance trained athletes in an Iranian male sample.